Analisis Pengaruh Kualitas Produk Dan Brand Image Terhadap Keputusan Pembelian Minuman Kekinian Haus Di Kabupaten Karawang - Supyan Assauri; Budi Kramadibrata (Politeknik Kampar, 2023)
This study investigates the influence of product quality and brand image on consumer interest. The data used are the results of statistical analysis, using the significance value (p-value) as a measure to assess the significance of the effects of these variables. The findings show that product quality has a significant impact on consumer interest. The study also reveals that brand image has a significant effect on consumer interest, with a p-value lower than the predetermined significance level. From these analyses, it can be concluded that changes in product quality can significantly influence consumer interest. Additionally, a positive brand image can enhance consumer interest in a product or brand. However, the study acknowledges several limitations, such as the partial nature of the findings and the lack of implying a cause-and-effect relationship between the examined variables.